STAT3 labels a subpopulation of reactive astrocytes required for brain metastasis. (July 2018) - Priego, Neibla; Zhu, Lucía; Monteiro, Cátia; Mulders, Manon; Wasilewski, David; Bindeman, Wendy; Doglio, Laura; Martínez, Liliana; Martínez-Saez, Elena; Cajal, Santiago; Megías, Diego; Hernández-Encinas, Elena; et al.
Abstract The brain microenvironment imposes a particularly intense selective pressure on metastasis-initiating cells, but successful metastases bypass this control through mechanisms that are poorly understood. Reactive astrocytes are key components of this microenvironment that confine brain metastasis without infiltrating the lesion. Here, we describe that brain metastatic cells induce and maintain the co-option of a pro-metastatic program driven by signal transducer and activator of transcription 3 (STAT3) in a subpopulation of reactive astrocytes surrounding metastatic lesions. These reactive astrocytes benefit metastatic cells by their modulatory effect on the innate and acquired immune system. In patients, active STAT3 in reactive astrocytes correlates with reduced survival from diagnosis of intracranial metastases. Blocking STAT3 signaling in reactive astrocytes reduces experimental brain metastasis from different primary tumor sources, even at advanced stages of colonization. We also show that a safe and orally bioavailable treatment that inhibits STAT3 exhibits significant antitumor effects in patients with advanced systemic disease that included brain metastasis. Responses to this therapy were notable in the central nervous system, where several complete responses were achieved. Given that brain metastasis causes substantial morbidity and mortality, our results identify a novel treatment for increasing survival in patients with secondary brain tumors. Reactive astrocytes expressing STAT3 support the metastatic growth of tumor cells colonizing the brain and can be pharmacologically targeted to improve the clinical management of patients with secondary brain tumors.